Measurement‐Based Synthesis of Facial Microgeometry. (6th May 2013) - Graham, Paul; Tunwattanapong, Borom; Busch, Jay; Yu, Xueming; Jones, Andrew; Debevec, Paul; Ghosh, Abhijeet
Abstract: We present a technique for generating microstructure‐level facial geometry by augmenting a mesostructure‐level facial scan with detail synthesized from a set of exemplar skin patches scanned at much higher resolution. Additionally, we make point‐source reflectance measurements of the skin patches to characterize the specular reflectance lobes at this smaller scale and analyze facial reflectance variation at both the mesostructure and microstructure scales. We digitize the exemplar patches with a polarization‐based computational illumination technique which considers specular reflection and single scattering. The recorded microstructure patches can be used to synthesize full‐facial microstructure detail for either the same subject or to a different subject. We show that the technique allows for greater realism in facial renderings including more accurate reproduction of skin's specular reflection effects.